Annotated record of the detailed examination of Mn deposits from DSDP Site 48, Leg 6 (Cores 48-1) - Bruce C Heezen; A G Fischer; Robert E Boyce; David Bukry; Robert G Douglas; Robert E Garrison; S A Kling; Valery A Krasheninnikov; Alexander P Lisitzin; Anthony C Pimm (PANGAEA, 1971)
Having been stopped by chert in the Maestrichtian at Site 47, a site was looked for which would give an adequate Cenozoic thickness for satisfactory spudding-in, yet promised to lead from this into an older part of the section. This is the first record of Middle Maestrichtian in pelagic carbonate facies from the Northwest Pacific and surrounding lands, a matter of paleontologic-biostratigraphic importance.
Supplement to: Heezen, BC et al. (1971): Site 48. In: Fischer, A.G.; et al., Initial Reports of the Deep Sea Drilling Project, 6, Initial Reports of the Deep Sea Drilling Project, 6, U.S. Government Printing Office, VI, 145-169, https://doi.org/10.2973/dsdp.proc.6.106.1971